Copper acetate-facilitated transfer-free growth of high-quality graphene for hydrovoltaic generators. Issue 7 (8th September 2021) - Shan, Jingyuan; Fang, Sunmiao; Wang, Wendong; Zhao, Wen; Zhang, Rui; Liu, Bingzhi; Lin, Li; Jiang, Bei; Ci, Haina; Liu, Ruojuan; Wang, Wen; Yang, Xiaoqin; et al.
Abstract: Direct synthesis of high-quality graphene on dielectric substrates without a transfer process is of vital importance for a variety of applications. Current strategies for boosting high-quality graphene growth, such as remote metal catalyzation, are limited by poor performance with respect to the release of metal catalysts and hence suffer from a problem with metal residues. Herein, we report an effective approach that utilizes a metal-containing species, copper acetate, to continuously supply copper clusters in a gaseous form to aid transfer-free growth of graphene over a wafer scale. The thus-derived graphene films were found to show reduced multilayer density and improved electrical performance and exhibited a carrier mobility of 8500 cm 2 V −1 s −1 . Furthermore, droplet-based hydrovoltaic electricity generator devices based on directly grown graphene were found to exhibit robust voltage output and long cyclic stability, in stark contrast to their counterparts based on transferred graphene, demonstrating the potential for emerging energy harvesting applications. The work presented here offers a promising solution to organize the metal catalytic booster toward transfer-free synthesis of high-quality graphene and enable smart energy generation. Abstract : An effective approach by utilizing metal-containing species, copper acetate, to catalyze the transfer-free graphene growth over dielectric substrates is put forward. Droplet-based hydrovoltaic electricity generator devices based on thus-grown graphene manifest robust voltage output and long cyclic stability.